From the Great Recession to Labour Market Recovery. : Issues, Evidence and Policy Options. - Islam, Iyanatul (International Labour Office, 2011)
The Great Recession was one of the most traumatic global events of the first decade of the twenty-first century. This book showcases research undertaken by leading experts on the macroeconomic and labour market dimensions of the financial crisis of 2007-2009. It provides a global overview, interpreting the causes, consequences and policy responses to the Great Recession from the perspective of both developing and developed countries.